2019
DOI: 10.3389/fmicb.2019.00242
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Uncultivated Majority in Antarctic Soils: Toward a Synergistic Approach

Abstract: Although Antarctica was once believed to be a sterile environment, it is now clear that the microbial communities inhabiting the Antarctic continent are surprisingly diverse. Until the beginning of the new millennium, little was known about the most abundant inhabitants of the continent: prokaryotes. From then on, however, the rising use of deep sequencing techniques has led to a better understanding of the Antarctic prokaryote diversity and provided insights in the composition of prokaryotic communities in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 200 publications
7
33
0
2
Order By: Relevance
“…Bacteroidetes, Proteobacteria, Actinobacteria, and Acidobacteria, with the dominant taxa members of the families Solirubrobacteraceae, Blastocatellaceae, Chitinophagaceae, and Rubrobacteriaceae ( Figure 1C, Data S1). The composition of the bacterial communities in these soils is consistent with results obtained using similar cultivation-independent analyses of other Antarctic soils, including those found in the McMurdo Dry Valley region (11,21,22). The fungal communities in these soils were dominated by members of the Ascomycota and Basidiomycota phyla, including members of the families Herpotrichiellaceae, Trapeliaceae, Verrucariaceae, Filobasidiaceae, Mortierellaceae, Stereocaulaceae ( Figure S1, Data S2).…”
Section: Microbial Communities Of the Shackleton Glacier Regionsupporting
confidence: 83%
See 1 more Smart Citation
“…Bacteroidetes, Proteobacteria, Actinobacteria, and Acidobacteria, with the dominant taxa members of the families Solirubrobacteraceae, Blastocatellaceae, Chitinophagaceae, and Rubrobacteriaceae ( Figure 1C, Data S1). The composition of the bacterial communities in these soils is consistent with results obtained using similar cultivation-independent analyses of other Antarctic soils, including those found in the McMurdo Dry Valley region (11,21,22). The fungal communities in these soils were dominated by members of the Ascomycota and Basidiomycota phyla, including members of the families Herpotrichiellaceae, Trapeliaceae, Verrucariaceae, Filobasidiaceae, Mortierellaceae, Stereocaulaceae ( Figure S1, Data S2).…”
Section: Microbial Communities Of the Shackleton Glacier Regionsupporting
confidence: 83%
“…extracting DNA from larger sample volumes, testing a range of different extraction kits and PCR protocols). Instead, we note that while all of these soils have very low biomass, 20% of the soils failed to yield detectable amounts of amplifiable bacterial, archaeal, or fungal DNA using techniques that are routinely used to successfully characterize microbial communities in soils from different regions of Antarctica (8,22,26).…”
Section: Microbial Communities Of the Shackleton Glacier Regionmentioning
confidence: 92%
“…It has been suggested that the extreme abiotic pressures of the environment such as temperature, desiccation stress and UV radiation are dominant drivers of both the diversity and function of cold-adapted bacterial communities in terrestrial polar deserts (5–7). Similarly, biotic interactions such as competition, symbioses, horizontal gene transfer (HGT) and predation have also been shown to play a role in the distribution and diversity of microbial communities in these soil ecosystems (810). The presence of viruses, including bacteriophages, in these cold hyper-arid desert soils potentially adds an additional layer of complexity to the microbial system, but the extent to which phage-host interactions play a role in shaping community compositions and processes in cold desert soil niches remains a matter of speculation (11, 12).…”
Section: Introductionmentioning
confidence: 99%
“…Some species form morphologically distinct resting structures that are commonly characterized by thickened cell walls or accumulations of extracellular polymeric substances (15). For instance, members of Actinobacteria and Firmicutes, Gram-positive bacterial phyla widely found in drylands (7,13,14,16), are well known for their ability to form highly stress-resistant spores (17,18). Consistently, these sporulating taxa are among the most common groups identified in desert soils (19)(20)(21)(22) based on both conventional cultivation studies and modern molecular phylogenetic analyses.…”
mentioning
confidence: 97%
“…Despite photoautotrophs typically being low in abundance, diverse and viable microbial communities are present in the topsoils of most deserts, including the hyper-arid soils of the Atacama Desert (13) and Antarctic Dry Valleys (14). As summarized in Fig.…”
mentioning
confidence: 99%